2015
DOI: 10.15171/rdme.2015.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Emotional Intelligence and Clinical Competencies of Nursing Students in Tabriz Nursing and Midwifery School

Abstract: Introduction: Preparing students to take over job responsibilities is one of the most challenging duties of nursing schools. The focus of nursing education should be on helping students to achieve high levels of competence in nursing care and identify factors for reinforcing it. Since desirable results have not been reported on clinical competencies of nursing students, achieving skills to control their emotions could be effective. Thus, this study aimed to investigate the relationship between emotional intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…These findings are reflected in Benner's (1984) "novice to expert" theory, which suggests that, with experience, a beginner can move from a position of novice understanding to one of increased competence. In contrast, these results disagree with Farshi et al (2015), who reported no significant relationship between clinical competence and the variable of gender. Overall, this study found a positive correlation between self-efficacy and clinical competence.…”
Section: Discussioncontrasting
confidence: 96%
“…These findings are reflected in Benner's (1984) "novice to expert" theory, which suggests that, with experience, a beginner can move from a position of novice understanding to one of increased competence. In contrast, these results disagree with Farshi et al (2015), who reported no significant relationship between clinical competence and the variable of gender. Overall, this study found a positive correlation between self-efficacy and clinical competence.…”
Section: Discussioncontrasting
confidence: 96%
“…11 The finding of the study showed that most of the respondents 108 (81.8%) had high level of emotional intelligence which is similar with the findings of the study conducted in Iran which showed mean EI score 109.09 indicating high level of EI. 12 Similarly, the finding of the present study is consistent with the findings of the study which showed that more than half of the studied students had moderate levels of emotional intelligence. 13 In the same line the findings of the study among baccalaureate students at the Faculty of Nursing, Alexandria University indicated that the majority of the studied students in the four semesters had moderate levels of EI.…”
Section: Discussionsupporting
confidence: 92%
“…Another interesting statistical data extracted from the GET is that students from less advanced periods of the course obtained a higher average than students from more advanced periods of the course in the 'Drive and Determination' dimension, meaning that students have entrepreneurial characteristics when they enter university such as thinking about alternative strategies, looking for solutions and enjoying new challenges, but they lose those characteristics during the course. It is necessary for the HEI curriculum to include curricular units which encourage students to have entrepreneurial characteristics and interpersonal skills, because this makes a difference in the selection processes of employing institutions (1) .…”
Section: Discussionmentioning
confidence: 99%
“…The development of skills for care management is increasingly important for inserting nurses into the job market. In this sense, the challenge of helping students achieve high levels of competence in professional practice is up to the nursing schools (1) . For this reason, nursing education in Brazil has been undergoing transformations in training workers with an adequate profile to the population's health demands (2) .…”
Section: Introductionmentioning
confidence: 99%